Borisoglebsk. Identity of a small town - Kapustin, Petr; Astashov, Denis (project baikal, 2021)
Borisoglebsk is a district center in the Voronezh region, a typical provincial town in the Black Earth region of Russia. Despite its turbulent history, the town managed to save most of its historical and cultural wealth. Today this small town is “frozen” in anticipation of upcoming changes. The changes are coming together with large-scale national projects, building initiatives and the general tendency towards improvements and contemporary design. The authors discuss the measure of adequacy of possible development strategies for the values of the urban fabric woven by a long and slow accumulation of qualities “in situ”.